Assembling Kidney Tissues from Cells: The Long Road from Organoids to Organs - Hariharan, Krithika; Kurtz, Andreas; Schmidt-Ott, Kai M. (Frontiers in Cell and Developmental Biology, 2015)
The field of regenerative medicine has witnessed significant advances that can pave the way to creating de novo organs. Organoids of brain, heart, intestine, liver, lung and also kidney have been developed by directed differentiation of pluripotent stem cells. While the success in producing tissue-specific units and organoids has been remarkable, the maintenance of an aggregation of such units in vitro is still a major challenge. While cell cultures are maintained by diffusion of oxygen and nutrients, three- dimensional in vitro organoids are generally limited in life-span, size, and maturation due to the lack of a vascular system. Several groups have attempted to improve vascularization of organoids. Upon transplantation into a host, improved ramification of host blood supply was shown in these organoids. Moreover, sustained circulation allows cells of an in vitro established renal organoid to mature and gain functionality in terms of absorption, secretion and filtration. Thus, the coordination of tissue differentiation and vascularization within developing organoids is an impending necessity to ensure survival, maturation and functionality in vitro and tissue integration in vivo. In this review, we inquire how the foundation of circulation is laid down during the course of organogenesis, with special focus on the kidney. We will discuss whether nature offers a clue to assist the generation of a nephro-vascular unit that can attain functionality even prior to receiving external blood supply from a host. We revisit the steps that have been taken to induce nephrons and provide vascularity in lab grown tissues. We also discuss the possibilities offered by advancements in the field of vascular biology and developmental nephrology in order to achieve the long-term goal of producing transplantable kidneys in vitro.